Creep Fatigue of Solder Joints in Electronic Assemblies (Global Journals of Research in Engineering, 2024)
Electronic assembly is formed by mechanically joining and hence electrically interconnecting integrated circuit components onto printed circuit board using arrays of solder joints Differential thermal expansion between the integrated circuit component and the printed circuit board leads to failure of solder joints through the combined mechanisms of creep and fatigue This manuscript condenses the recent advances in creep fatigue analysis of solder joints in electronic assemblies into two major analyses thermomechanical analysis and creep fatigue life modelling The analytical thermomechanical analysis models an electronic assembly as a sandwich structure By modelling the actual geometry of solder joints it has found stout hourglass to be the ideal shape for solder joints that could reduce the magnitude of stress by 80 compared to the standard barrel-shape solder joints The new creep integrated fatigue equation integrates the fundamental equation of creep into fatigue life equation and has been shown to model very well the creep fatigue of solder alloy More valuably this methodology can be generalised to integrate general aggravating forces into fatigue life equation It can be further generalised to integrate multiple aggravating forces into fatigue equation
Keywords: thermomechanical analysis; environmental fatigue; optimum shape; life prediction; shear compliance